2021
DOI: 10.21037/apm-21-700
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in antimicrobial use associated with a multifaceted antimicrobial stewardship programme in a tertiary teaching hospital in Shanghai: a segmented regression analysis

Abstract: Background: Rational use of antibiotics received great attention in China, therefore the multifaceted antimicrobial stewardship (MAMS) is urgently required in hospital management. We conducted this study to assess the impact of a MAMS programme on antimicrobial use in a tertiary teaching hospital in Shanghai.Methods: This retrospective observational study was conducted at a tertiary teaching hospital in Shanghai. The MAMS programme involved multifaceted interventions consisting of a quality premium with financ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(18 citation statements)
references
References 19 publications
(27 reference statements)
0
18
0
Order By: Relevance
“…Full text of remaining 66 articles were reviewed, and finally, 16 articles were included in this systematic review ( 13 28 ) ( Figure 1 ). Eight studies reported only hospital-based results ( 13 , 14 , 23 28 ), nine reported only community-level antibiotic consumption ( 14 22 ), and one [conducted in England ( 14 )] reported antibiotic consumption in both hospitals and communities ( Tables 2 , 3 ). Although we did not limit the studies to the year 2020, we could not find any study that reported antibiotic consumption in 2021 through the systematic review.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Full text of remaining 66 articles were reviewed, and finally, 16 articles were included in this systematic review ( 13 28 ) ( Figure 1 ). Eight studies reported only hospital-based results ( 13 , 14 , 23 28 ), nine reported only community-level antibiotic consumption ( 14 22 ), and one [conducted in England ( 14 )] reported antibiotic consumption in both hospitals and communities ( Tables 2 , 3 ). Although we did not limit the studies to the year 2020, we could not find any study that reported antibiotic consumption in 2021 through the systematic review.…”
Section: Resultsmentioning
confidence: 99%
“…These studies, except for Murgadella-Sancho et al, reported an increase in antibiotic consumption in 2020. Only one study from China reported that the continuous implementation of antibiotic stewardship programs since 2019 throughout 2020 resulted in the reduction of overall antibiotic consumption in 2020 ( 23 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, the current status of AMS management in surgery is of major significance to the rational use of antibiotics in the future. Our former studies have finished to build a management and control mode in comprehensive hospital AMS ( 8 ), however, AMS management from surgical perspective is lacking. Therefore, we performed this study to provide a structured analysis of AMS research in the surgical field both from macroscopic and microscopic aspects, to infer future trends and identify shifts in this field.…”
Section: Introductionmentioning
confidence: 99%